Effect of Extract Meat Dates (Phoenix dactylifera L.) to Oxytocin Levels in Pregnant Mice (Mus musculus L.) - Eva Agustina; Risa Purnamasari; Nova Lusiana (Humanistic Network for Science and Technology (HNST), 2017)
The process of spontaneous labor is sensitive to the oxytocin hormone that causes uterine smooth muscle contraction as a receptor for the start of labor. Dates contains source of carbohydrates are simple sugars, iron, potassium, selenium, calcium, and flavonoids. The purpose of this study was to determine the effect of date’s extracts (Phoenix dactilifera L) to the oxytocin hormone day 19 of gestation age of mice (Mus musculus L). This experiment devide dose of date extract into four groups, group I : control (no treatment), group II: 3 dates (3.12 mg/kg), group III 5 dates (5.2 mg/kg), and group IV 7 dates (7.28 mg/kg) to the oxytocin hormone. The research method is done by extracting palm ajwa with methanol. Treat made orally at the age of 14-19 days gestation. Measurement of oxytocin levels using ELISA at the age of pregnancy 19 days, showed the average number of levels of the oxytocin hormone in group I in the amount of 126.494 ng / L, the second group is equal to 124.169 ng / L, group III amounting to 129.041 ng / L, and group IV is equal to 132.252 ng / L. Overall extract dates with various doses of the treatment led to increased levels of the oxytocin hormone in mice. However, these increases did not show a significant effect, although the hormones oxytocin on uterine tissue of mice kept rising. Keywords: Dates extract, Oxitocin levels, Pregnant mice